Victims and Perpetrators of Cyber Harassment: The Role of Power and Control and the Use of Techniques of Neutralization. Issue 5 (4th May 2023) - van Baak, Carlijn; Maher, Cooper A.; Protas, Michelle E.; Hayes, Brittany E.
ABSTRACT: Cyber harassment is a common problem among younger populations and women. While scholars have noted that cyber harassment may be an attempt to demonstrate power and control, it remains unclear if that is the case from the victim's and perpetrator's perspective. Relying on open-ended responses from a sample of college students, we use a validated instrument to qualitatively examine if victims of cyber harassment (N = 170) perceived their victimization to center on aspects of power and control. Additionally, we examine if students who engaged in cyber harassment (N = 33) minimize their behaviors by employing techniques of neutralization and identify how these efforts may overlap with power and control (i.e., threats, checking movements). Findings reveal that one out of three victims reported controlling behaviors, which were commonly experienced by women and perpetrated by men, and regularly included severe controlling techniques. We additionally found that perpetrators of cyber harassment frequently engaged in techniques of neutralization. The most common technique was denial of injury. Implications and directions for future research are discussed.